Quiz (1 point)
Given that:
(a + b) + c = d
a = e
Prove that:
(e + b) + c = d
The following properties may be helpful:
- (a + b) + c = a + (b + c)
- a + b = b + a
- (a + b) + c = a + (b + c)
if a = b, then b = a
if the following are true:
- a = b
- b = c
then a = c
if the following are true:
- a = b
- b = c
then a = c
if the following are true:
- a + b = c
- b = d
then a + d = c
if a + b = c, then b + a = c
if the following are true:
- a = b
- b = c
then a = c
Please write your proof in the table below. Each row should contain one claim. The last claim is the statement that you are trying to prove.